Role of Oral Bacteria in Mediating Gemcitabine Resistance in Pancreatic Cancer - Geng Xu; Yaling Jiang; Chen Sun; Bernd W. Brandt; Kamran Nazmi; Luca Morelli; Giulia Lencioni; Elisa Giovannetti; Dongmei Deng (Biomolecules)
Oral microbiota have been implicated in pancreatic ductal adenocarcinoma (PDAC) and may contribute to chemotherapy resistance. While previous studies attributed bacteria-induced resistance to indirect host modulation, recent findings suggest a direct mechanism. Escherichia coli expressing long-form cytidine deaminase (CDDL) can degrade gemcitabine, a chemotherapeutic agent, into a non-toxic form, leading to resistance. In contrast, bacteria carrying short form (CDDS) or lacking CDD did not induce resistance. This study investigates whether oral bacteria can cause gemcitabine resistance in PDAC cells through CDD-mediated degradation. Oral microbes associated with PDAC were selected based on CDD isoforms: Aggregatibacter actinomycetemcomitans carrying CDDL, Enterococcus faecalis, Streptococcus mutans, Porphyromonas gingivalis, all carrying CDDS, and Fusobacterium nucleatum lacking CDD. The selected microbes, along with wild-type and CDD-deficient E. coli, were co-incubated with gemcitabine to assess its degradation and PDAC cell proliferation. A. actinomycetemcomitans fully degraded gemcitabine and induced resistance. Surprisingly, CDDS-expressing oral bacteria partially degraded gemcitabine in a strain-dependent manner. Expressing either CDDL or CDDS in CDD-deficient E. coli resulted in equivalent gemcitabine degradation and resistance, indicating that CDD function is independent of isoform length. These findings highlight the role of oral bacteria in gemcitabine resistance and the need for strategies to mitigate microbial-driven resistance in PDAC treatment.